Predicting pharmacoresistance in pediatric epilepsy - Elaine Wirrell (2013)
Summary Approximately 20% of children with epilepsy will be pharmacoresistant. The impact of intractable epilepsy extends far beyond just the seizures to result in intellectual disability, psychiatric comorbidity, physical injury, sudden unexpected death in epilepsy ( SUDEP ), and poor quality of life. Various predictors of pharmacoresistance have been identified; however, accurate prediction is still challenging. Population‐based epidemiologic studies show that the majority of children who develop pharmacoresistance do so relatively early in the course of their epilepsy. However, approximately one third of children who initially appear pharmacoresistant in the first few years after epilepsy onset will ultimately achieve seizure freedom without surgery. The most significant predictor that early pharmacoresistance will not remit is the presence of a neuroimaging abnormality. Such children should be strongly considered for surgical evaluation.